Whole-eye electrical stimulation therapy preserves visual function and structure in P23H-1 rats - Hanif, Adam M.; Kim, Moon K.; Thomas, Joel G.; Ciavatta, Vincent T.; Chrenek, Micah; Hetling, John R.; Pardue, Machelle T. (Experimental eye research, 2016)
Low-level electrical stimulation to the eye has been shown to be neuroprotective against retinal degeneration in both human and animal subjects, using approaches such as subretinal implants and transcorneal electrical stimulation. In this study, we investigated the benefits of whole-eye electrical stimulation (WES) in a rodent model of retinitis pigmentosa. Transgenic rats with a P23H-1 rhodopsin mutation were treated with 30 min of low-level electrical stimulation (4 μA at 5 Hz; n = 10) or sham stimulation (Sham group; n = 15), twice per week, from 4 to 24 weeks of age. Retinal and visual functions were assessed every 4 weeks using electroretinography and optokinetic tracking, respectively. At the final time point, eyes were enucleated and processed for histology. Separate cohorts were stimulated once for 30 min, and retinal tissue harvested at 1 h and 24 h post-stimulation for real-time PCR detection of growth factors and inflammatory and apoptotic markers. At all time-points after treatment, WES-treated rat eyes exhibited significantly higher spatial frequency thresholds than untreated eyes. Inner retinal function, as measured by ERG oscillatory potentials (OPs), showed significantly improved OP amplitudes at 8 and 12 weeks post-WES compared to Sham eyes. Additionally, while photoreceptor segment and nuclei thicknesses in P23H-1 rats did not change between treatment groups, WES-treated eyes had significantly greater numbers of retinal ganglion cell nuclei than Sham eyes at 20 weeks post-WES. Gene expression levels of brain-derived neurotrophic factor (BDNF), caspase 3, fibroblast growth factor 2 (FGF2), and glutamine synthetase (GS) were significantly higher at 1 h, but not 24 h after WES treatment. Our findings suggest that WES has a beneficial effect on visual function in a rat model of retinal degeneration and that post-receptoral neurons may be particularly responsive to electrical stimulation therapy. •Whole-eye electrical stimulation (WES) preserved visual function in P23H-1 rats.•WES preserved inner retinal function, as measured with ERG, in P23H-1 rats.•WES preserved retinal ganglion cell layer nuclei, but not photoreceptors in P23H-1 rats.•WES acutely increased growth factor expression in the retina in P23H-1 rats.•Post-receptoral neurons may be most responsive to electrical stimulation therapy.